Arte e società nell’estetica dell’idealismo italiano - Paolo D’Angelo (Rivista di Estetica, 2022)
The theme of the relationship between art and society is certainly not a central topic in the aesthetic reflection of Italian neo-idealism. Neither in Croce nor in Gentile it is ever discussed at length, and the few writings in which it is addressed are brief and polemically oriented. This essay, however, proposes to discuss the few hints present in Croce and Gentile on this subject. First, the debate on the materialistic interpretation of history will be examined, to which both Croce and Gentile made important contributions at the end of the 19th century. Secondly, Croce’s own way of doing the history of literature will be discussed, showing the differences that distance him from the Desanctisian model and also from the model derived from the Hegelian Aesthetics. Croce’s way of making history of literature, indeed, aroused harsh criticism after World War II and provoked a request for a “return to De Sanctis”.Finally, but the theme will be only hinted at in the essay, a brief reference will be proposed to the opinions of Antonio Gramsci and his reading of Croce.